Understanding the training need analysis model at Panasonic AVC Networks (PAVCJM) Pasir Gudang Johor / Najatul Fareza Redzwan - Redzwan, Najatul Fareza (2017)
Panasonic AVC Networks Johor Malaysia Sdn. Bhd (PAVJCM) is known as Matsushita Audio Video (M) Sdn. Bhd. (MAV). PAVJCM was established in 21 December 1990 as the 14th Matsushita Company in Malaysia and the first Audio and Video Company in South Asia out of Japan. On 1 April 2003, MAV has changed their name to PAVJCM (Panasonic AVC Networks Johor Malaysia Sdn. Bhd.) because of Japanese policy and marketing strategy. PAVJCM was built for the purpose of creating technological brilliance in light and sound. Panasonic also has seven principles they are contributing to society, fairness and honesty, cooperation and team spirit, untiring effort for improvement, courtesy and humidity, and adaptability and gratitude. Other than that, this Company also practice 5S that is sorted, set in order, sustains, shine and standardize. The objective of this study is to understand the process of Training Need Analysis (TNA) used by Panasonic AVC Networks Pasir Gudang. Other than that, to compare the difference between Training Need Analysis (TNA) practices used at Panasonic with the TNA model structure Panasonic AVC Networks Pasir Gudang and to suggest the best Training Need Analysis (TNA) model for Panasonic AVC Networks Pasir Gudang and lastly, to compare the Training Need Analysis (TNA) Panasonic AVC Networks Pasir Gudang with Goldstein and Ford's model. As for research methodology the researcher used qualitative method, that's is interview, and observation to collect data and finding the result. The researcher has interview five employees at Panasonic AVC Networks Pasir Gudang Johor in the month of May. Lastly, for the findings, the first objective have been achieved by understanding the Training Need Analysis (TNA) process that has been implement in Panasonic itself. As for the second objective, there is a gap between the TNA practices with the model structure. Thirdly, the researcher suggest Goldstein and Ford's model of TNA to Panasonic and for the last objective there is a gap between the model structure TNA Panasonic with Goldstein and Ford's model.